Embracing innovation and advancing care: integrating learning health system principles into Inova Schar Heart and Vascular - O’Connor, Christopher M.; Rosner, Carolyn M.; Gill, Andrew; Speir, Alan M.; Neville, Richard F. (Frontiers in Cardiovascular Medicine, 2024)
Inova Schar Heart and Vascular has an unwavering commitment to delivering excellent cardiovascular care and has integrated principles of a learning health care system to develop our system of continuous process improvement and innovation. A learning health system integrates its internal experiences with external research to enhance patient outcomes, support the discovery of new treatments and care pathways, and deliver safer, more efficient, and more personalized care. Leveraging learning across health systems maximizes the impact, allowing cardiovascular teams to gain insights into the effectiveness of different treatment strategies. In this Frontiers in Cardiovascular Medicine compendium of articles, the team at Inova describe the spectrum of research and educational activities that have contributed to our progress as a learning cardiovascular health system and support our journey to deliver excellent cardiovascular care.